2015
DOI: 10.1136/bmjdrc-2015-000140
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the antibody response to influenza vaccination in older adults with type 2 diabetes

Abstract: ObjectiveType 2 diabetes mellitus (T2DM) is one of the most prevalent chronic inflammatory diseases of the elderly. Its development is related to the alteration of the immune system with aging characterized by immunosenescence and inflamm-aging. In turn, T2DM also alters the immune response. As a consequence, older people with T2DM are more susceptible to influenza and to its complications as compared with healthy controls. Vaccination against influenza has shown poor efficacy in the older population and even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 54 publications
2
58
2
1
Order By: Relevance
“…The influenza vaccine response was measured in T2D elderly individuals and compared to healthy age-matched controls (McElhaney et al 2015). Results showed no differences between T2D elderly and healthy elderly in the antibody response to the vaccine.…”
Section: CMV Infectious Diseases and Vaccine Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The influenza vaccine response was measured in T2D elderly individuals and compared to healthy age-matched controls (McElhaney et al 2015). Results showed no differences between T2D elderly and healthy elderly in the antibody response to the vaccine.…”
Section: CMV Infectious Diseases and Vaccine Responsesmentioning
confidence: 99%
“…In this cohort, CMV did not determine per se any functional alteration in clinical and functional parameters of participating elderly individuals. In the same study (McElhaney et al 2015), the antibody response to the vaccine was compared between CMV-seropositive and CMV-seronegative elderly participants. Results showed that both healthy and T2D CMV-seropositive individuals had a significant higher response, which was unexpected, suggesting that in addition to age and diabetic status, immunological history such as CMV status should be taken into account.…”
Section: CMV Infectious Diseases and Vaccine Responsesmentioning
confidence: 99%
“…Inconsistent findings of the impact of CMV on antibody responses to vaccination have been reported (Wald et al, 2013; Frasca et al, 2015; Furman et al, 2015; McElhaney et al, 2015; Haq et al, 2016). While the influenza B GMT was higher pre-vaccination in CMV − subjects, there was no difference in GMT fold increase (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The majority of older adults are seropositive for cytomegalovirus (CMV) (Staras et al, 2006) which may be a confounding factor in evaluating the immune response to influenza vaccination (Frasca et al, 2015; Furman et al, 2015; McElhaney et al, 2015; Haq et al, 2016). Persistent CMV infection has been shown to be a major driver of terminal differentiation of CD8 + T-cells (Derhovanessian et al, 2009; McElhaney et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Three clinical trials evaluating antibody responses to influenza vaccination in patients with diabetes were published in 2015 [65][66][67]. Overall, the data showed no difference in immunological efficacy across several groups varying in age and in the type of diabetes.…”
Section: Diabetes Mellitusmentioning
confidence: 96%